2021
DOI: 10.7759/cureus.17756
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Function, Mental and Physical Health in Recovered COVID-19 Patients Requiring Invasive Versus Non-invasive Oxygen Therapy: A Prospective Follow-Up Study Post-ICU Discharge

Abstract: BackgroundSurvivors of COVID-19 pneumonia may have residual lung injury and poor physical and mental health even after discharge. We hypothesized that COVID-19 severe acute respiratory distress syndrome (ARDS) patients needing mechanical ventilation may be at a greater risk of deterioration in pulmonary function, mental health, and quality of life (QOL). This study analyses the differences in pulmonary function, mental health, and QOL after recovery, in patients having received non-invasive oxygen therapy vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Studies assessing pulmonary function following ARDS and SARS-CoV-2 show heterogeneous results, however we noted a similar degree of obstructive and restrictive lung disease which was stable during the first year of recovery. This may be worst in patients receiving invasive mechanical ventilation 49 ; but this question goes beyond the scope of this review. Follow-up CT images have demonstrated pulmonary fibrotic changes, ground-glass opacification, and traction bronchiectasis 91 even up to 5 years after severe ARDS 92,93 .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Studies assessing pulmonary function following ARDS and SARS-CoV-2 show heterogeneous results, however we noted a similar degree of obstructive and restrictive lung disease which was stable during the first year of recovery. This may be worst in patients receiving invasive mechanical ventilation 49 ; but this question goes beyond the scope of this review. Follow-up CT images have demonstrated pulmonary fibrotic changes, ground-glass opacification, and traction bronchiectasis 91 even up to 5 years after severe ARDS 92,93 .…”
Section: Discussionmentioning
confidence: 97%
“…The 6 Minutes Walking test (6MWT) was the most common tool used to measure physical function in 15 studies 13,21,[47][48][49]56,58,62,65,66,71,74,77,78 with only one study 58 adding the 4-meter gait speed alongside it. The overall mean distance walked in 6 minutes was 401m (95% CI 363, 439; l 2 =99% P<0.001) at 3 months, 427m (95% CI 378, 476; l 2 =99% P<0.001) at 6 months and 410m (95% CI 385, 434; l 2 =99% P<0.001) at 12 months.…”
Section: Physical Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 Similarly, a study conducted at this center has reported modest impairments in QOL in patients with COVID-19 who were mechanically ventilated. 27 Studies have shown that COVID-19 leads to impairments in QOL that gradually show an improving trend. 28,29 Similar to results reported earlier in an Indian sample, in our study, QOL was most affected by the presence of pain/discomfort, followed by mobility problems, difficulties in self-care activities, difficulties in performing usual activities, and the presence of anxiety/ depression.…”
Section: Discussionmentioning
confidence: 99%